The impact of the Bratislava Emergency Court in Transylvania. News and refugees - Balogh, Judit (Egyháztörténeti Szemle, 2025)
The study deals with a question that has not yet been addressed in research. It attempts to investigate how the persecution of Protestants in Hungary, which began in 1671, appears in the correspondence and other documents of the Reformed elite of the Principality of Transylvania. It also aims to answer the question of how the Reformed nobility of Transylvania tried to help the persecuted Protestants in Hungary. The results of previous research indicate that the Transylvanian Reformed were aware of what was happening and tried to help in various ways. On the one hand, they took in persecuted refugees; on the other, they drew international attention to the events and in some cases even supported the provision of military aid.